Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

Organic amendments induce crop-specific soil biotic homogenization associated with SOC sequestration: Evidence from a 35-year intercropping experiment - Guizong Zhang; Jiudong Zhang; Rui-Peng Yu; Hao Yang; Xingguo Bao; Wenju Liang; Qi Li; Long Li (Soil and Tillage Research, 2026)

Phytochemical profiling of undescribed triterpenoids from Cyclocarya paliurus leaves: structural elucidation and metabolic regulation potential - Yiwei Wu; Huizhen Yang; Wenjie Shangguan; Wenting Zhang; Long Chen; Rui Min; Xinrong Fan; Yindi Zhu; Xiaojie Zheng; Yin Xiong; Tunhai Xu (Phytochemistry, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Study on the O2 migration pathway and critical product formation mechanism in the water immersion coal oxidation - Guo-yu Shi; Xin-xiao Lu; Guan Wang; Zhao Yang; Long He; Rui-nan Zhang (Fuel, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

An enhanced bounding surface model with modified plastic flow rule for cyclically loaded clay: Formulation, implementation, and dynamic finite element analysis - Kehao Chen; Rui Pang; Bin Xu; Long Yu; Yang Zhou (Computers and Geotechnics, 2026)

Machine learning-guided discovery of poly(ethylene terephthalate)-binding modules to enhance durable whole-cell degradation - Rui Long; Yaxin Tang; Chengyong Wang; Tangli Yang; Wei Liu; Ling Jiang (Bioresource Technology, 2026)

Overview of research on fire smoke diffusion and control in tunnels with different connection structures - Yongzheng Yao; Yiyuan Wang; Rui Wang; Luyao Tan; Tao Du; Lei Jiang; Kun He; Zihe Gao; Zeng Long (Tunnelling and Underground Space Technology, 2026)

Microwave coupled ultrasound pretreatment for enhancing acid leaching of ilmenite and its mechanism - Rui Liu; Long Xiang; Tao Long; Wenrong Xiang; Jiahao Hu; Li Li; Chunhui Han; Xingran Zhang (Minerals Engineering, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

Late Pleistocene landslide-dammed events in the Panzhihua-Wudongde reach of the Jinsha River in southeastern Tibetan: Implications for the origin of the Longjie Formation - Fenliang Liu; Hongshan Gao; Rui Yang; Wei Zhang; Yuehong Long; Wenfeng Xi (Geomorphology, 2026)

Enhanced stability of CH3NH3PbBr3 quantum dots for electrochemiluminescence detection of saxitoxin - Yu Han; Ting Zhang; Rui Kang; Xin Gao; Jiawei Liu; Qingchun Yin; Hongmei Cao; Long Wu (Food Chemistry, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

A biomimetic mineralized injectable hydrogel enables spatiotemporal dual-drug delivery for colorectal cancer therapy - Jing-Yu Feng; Rui Zhang; Jing-Ling Yang; Rui Lu; Kiran Thakur; Fei Hu; Yi-Long Ma; Jian-Guo Zhang; Zhao-Jun Wei (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Driving workload capacity of highway tunnel entrance and exit takeover under non-driving-related tasks: a multi-dimensional information coupling method - Shuangkai Zhu; Bo Liang; Jia An Niu; Rui Su; Haonan Long; Tao Deng; Mengdie Xu (Tunnelling and Underground Space Technology, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

A synthetic microbiome drives a multi-omics response to remediate 1,4-dithiane–contaminated soil and simultaneously suppresses antibiotic resistance genes - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Journal of Hazardous Materials, 2026)

Identification and stress-induced expression of Drosomycin and Termicin genes in Shelfordella lateralis - Tie-Long Xu; Rui Zhu; Zu-Liang Li; Cao Zhou (Journal of Asia-Pacific Entomology, 2026)

Overcoming mass-transfer bottlenecks in thick electrodes via in-situ growth of high-entropy sulfides on 3D freeze-printed nickel frameworks - Long-Zhe Wei; Yi-Ting Zhang; Hui Sun; Rui-Fen Guo; Ping Shen (Chemical Engineering Journal, 2026)

Bioinspired core-shell structured electrospun fibers guide neural stem/progenitor cell lineage development for spinal cord injury repair - Jiaxin Chen; Zilong Rao; Rui Cui; Rongli Deng; Jing Zhou; Daping Quan; Xipeng Guan; Houqing Long; Ying Bai (Chemical Engineering Journal, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Dynamic response of muscle-inspired hierarchical tubular structure under lateral shock loading - Chang Ye Ni; De Long Cheng; Jian Hong Zhang; Gao Meng Cai; Rui Zhang; Tian Jian Lu (Engineering Structures, 2026)

Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Phosphorus-solubilizing Acinetobacter strains from Chinese medicine residues enhance tomato growth and rhizosphere microbial diversity - Hongxia Ding; Yulan Huang; Rui Zhao; Yanhong Wang; Yibo Huang; Sha Long; Hexin Feng; Guiwen Gao; Lingqi Meng (Biocatalysis and Agricultural Biotechnology, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Research progress on the preparation, modification, and pollutant adsorption removal applications of waste tire pyrolysis char - Tao Wang; Lixin Qian; Rui Hao; Xiangjie Gao; Xiangyang Xu; Hexi Zhao; Hongming Long (Process Safety and Environmental Protection, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Apatite-doped cyanobacterial biochar for treating smelting site pollution: A “win–win” strategy for cyanobacteria resource recovery and heavy metal mitigation - Rui Deng; Haoyang Deng; Wanning Ye; Qingsheng Xu; Long Du; Shu Wang; Zhengbo Yue; Wentao Wu (Environmental Geochemistry and Health, 2026)

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Stress Interference between Multi-radial Boreholes During Hydraulic Fracturing in Multilayered Reservoirs Based on the Discrete Lattice Method - Tengda Long; Xiaoguang Wu; Yazhou Shen; Zixiao Xie; Zhongwei Huang; Gensheng Li; Rui Yang; Zhaowei Sun; Tao Pan; Naikun Hu; Xiaohua Wang (Rock Mechanics and Rock Engineering, 2026)

A new seco -norlignan and a rare ring B aromatic 1(10→6) abeo -ergostane-type steroid from Tarlmounia elliptica - Qiao-Long Hao; Han-Mei Bai; Lei Miao; Shuang Yao; Chuan-Rui Zhang (Natural Product Research, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Biofilm-suspension syntrophy drives synergistic electro-fermentation through engineered spatial division of labor for concurrent carbon recovery and pollutant degradation - Jiayu Gu; Jiying Guo; Rui Peng; Yang Wu; Min Long; Xiong Zheng; Haining Huang; Yinguang Chen (Water Research, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Natural polysaccharide-modified oral pH-sensitive ZIF-8 delivery system for targeted release of lutein liposomes in the gastrointestinal tract - Lanxin Zhang; Shengnan Wang; Jingyi Long; Lina Yang; Jun Li; Lu Han; Rui Wang; Xiaohui Zhao; He Liu (Food Chemistry, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

Erratum to “Evidence of shallow subsurface ice at Tianwen-1 landing site” [Earth and Planetary Science Letters 678 (2026)/EPSL 119832] - Xindong Meng; Ling Zhang; Yi Xu; Iraklis Giannakis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Deletion of the SHORT Syndrome Gene Prkce Results in Brain Atrophy and Cognitive and Motor Behavior Deficits in Mice - Yu-Long Bao; Wei-Peng Duan; Yan Yang; Zhijie Lin; Ying Shen; Rui Zheng; Xin-Tai Wang (Neuroscience Bulletin, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Ultra-highly specific and visual detection of Vibrio pathogens in Porphyra using RPA-coupled CRISPR-LbaCas12a-LFD system - Xu-Xu Luo; Hai-Long Huang; Qi-Qin Liu; Hoi-Yan Kwok; Hai-Tao Ma; Hai-Bo Jiang; Rui Yang (Aquaculture, 2026)

Realization of elastic Weyl semimetal phases with skyrmion spin textures - Yuang Pan; Liang Si; Miao Yang; Ning Han; Li Zhang; Qiaolu Chen; Rui Zhao; Fujia Chen; Yudong Ren; Wenhao Li; Yuze Hu; Mingyu Tong; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Dynamic analysis for monopile offshore wind turbine under combined wind-wave-seismic loading: Effects of clay cyclic degradation and shakedown - Kehao Chen; Rui Pang; Cun Hu; Long Yu; Tianju Wang; Yang Zhou; Bin Xu (Ocean Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Self-assembled 8-shogaol/curcumin nanoparticles via hydrogen bonding: enhanced stability and sustained release in vitro - Rui Zhang; Jing-Yu Feng; Kiran Thakur; Fei Hu; Jian-Guo Zhang; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Reduction of regulatory B cells is associated with high-risk clinical stratification in antiphospholipid syndrome patients - Rui Ma; You-yang Wang; Jing-hong Feng; Wen-yi Li; Yan Long (Immunologic Research, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

Soil type regulates the development and insecticide susceptibility of Spodoptera frugiperda by modulating maize growth and nutritional content - Shi-Wen Deng; Mohammed Esmail Abdalla Elzaki; Wei Liang; Muhammad Hafeez; Wan-Ting Li; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2026)

Oxidized- and hydroxylated-pennogenin saponins from the rhizomes of Paris fargesii and their hemostatic activity - Ling-Ling Yu; Lijin Jiao; Yan-Xi Li; Xu-Hong Li; Shan-Shan Ling; Long-Gao Xiao; Rui-Qi Liu; Wei Ni; Huan Yan; Yunheng Ji; Hai-Yang Liu (Phytochemistry, 2026)

Leaching mechanism and kinetics investigation of ilmenite leaching assisted by iron powder - Tao Long; Long Xiang; Rui Liu; Congxue Tian; Li Li; Jiesong Liu; Wenrong Xiang (Minerals Engineering, 2026)

A general framework for designing and assessing sustainable and diversified cropping systems: Bridging knowledge-driven, model-aided, and participatory approaches - Zhengyuan Liang; Bowen Ma; Rui-Peng Yu; Yuewen Huo; Shingirai Mudare; Feiyu Ying; Long Li; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Evidence of shallow subsurface ice at Tianwen-1 landing site - Xindong Meng; Ling Zhang; Yi Xu; Giannakis Iraklis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

Interfacial charge threshold induced high-safety energetic co-particles - Hao-Rui Zhang; Yingqi Mao; Minghui Dai; Djalal Trache; Xu Zhao; Zhijian Yang; Qi-Long Yan (Chemical Engineering Journal, 2026)

Multi-frequency controlled-source electromagnetic fast forward modeling in general anisotropic media - Hang-rui Shen; Feng Zhou; Zhi-yong Zhang; Yan Li; Hui Chen; Ying-ying Zheng; Hai-long Ye (Applied Geophysics, 2026)

The wave-induced heat transport in the global ocean - Rui Li; Kejian Wu; Qingxiang Liu; Jin Liu; Shang-Min Long; Jian Sun; Alexander V. Babanin (Ocean Modelling, 2026)

Removal characteristics and functional bacterial community analysis of novel two-stage integrated biological reactor and two-stage anoxic–oxic systems feeding with livestock farming wastewater - Zhenxing Zhong; Wenzhe Liu; Yanxu Zhu; Jingjing Liu; Chunjie Zhang; Rui Wang; Nanshan Yang; Xuejun Long; Peng Yu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu; et al. (Journal of Water Process Engineering, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Can saturated fatty acids spare essential fatty acids in freshwater fish? Evidence from growth, metabolism and gut microbiota in common carp (Cyprinus carpio) - Yang Long; Zhiyi Cheng; Rui Li; Zeliang Su; Chaobin Qin; Guoxing Nie; Yuanyou Li; Dizhi Xie (Animal Feed Science and Technology, 2026)

The candidate effector Bd_A04480 contributes to Botryosphaeria dothidea-induced postharvest soft rot in kiwifruit by increasing virulence and suppressing plant immunity - Hong Tan; Jinhuang Song; Juanrong Qin; Shufeng Du; Rui Yang; Xiaoqing Dong; Zhibo Zhao; Youhua Long; Rong Fan (Postharvest Biology and Technology, 2026)

A unified density-aware network for stored-grain pest detection with intelligent risk assessment - Long Chen; Rui Li; Chengjun Xie; Peng Chen; Jie Zhang; Jianming Du; Hongbo Chen; Runsheng Qi; Jiahui Sun (Journal of Stored Products Research, 2026)

A unified hybrid deterministic-stochastic inversion methodology - Chao Zhuang; Long Yan; Huiyang Qiu; Rui Hu; Jiangbo Han; Huan Song; Zhifang Zhou; Jinguo Wang; Walter A. Illman (Journal of Hydrology, 2026)

Flash joule heating driven oxygen vacancy engineering in siloxene toward ultra-stable lithium-ion batteries - Quanqiang Yuan; Chengcheng He; Rui Sun; Jianlin Liang; Yaoxiang Shang; Longqing Zhang; Xingzhi Long; Yujie Zou; Bingkun Zang; Xucai Yin; Kelei Huang; Zhangfa Tong; et al. (Chemical Engineering Journal, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Does perceived proximity to urban facilities still matter to individuals' daily activities in the information age? - Kunbo Shi; Rui Shao; Yinhua Tao; Long Cheng; Tianren Yang (Journal of Transport Geography, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Xylo-oligosaccharide utilization by Weissella kandleri YT103: Transcriptomic analysis and intestinal barrier protection - Xin-rui Zhang; Shuang-shuang Cui; Long-fen Yin; Gui-zhen Gong; Jian-xia Yang; Yang Chen; Yuan-ting Zhu (Food Research International, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Radial borehole fracturing in the multilayered shale oil reservoir based on a 3D discrete lattice model - Zixiao Xie; Tengda Long; Xiaoguang Wu; Zhongwei Huang; Gensheng Li; Xianzhi Song; Rui Yang; Tao Pan; Wenchao Zou; Zhaowei Sun; Yaoyao Sun; Naikun Hu; et al. (Engineering Geology, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Lithium nitrate-stabilized electrolyte enabling wide-temperature and high-voltage lithium-ion batteries - Zhaojun Liu; Jiaxuan Feng; Rui Yang; Shen-ao Wang; Xiaochen Wu; Xiangyu Zhang; Sujuan Cheng; Ning Liu; Teng Long; Pengchao Si (Chemical Engineering Journal, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Interpretable liquefaction prediction model based on stacking algorithm - Xiao Long; Rui Sun; Tong Zheng; Yu Wang; Zhaocheng Zhong (Earth Science Informatics, 2025)

Zircon U-Pb Ages and Sr-Nd-Hf Isotopes Geochemistry of I-Type Granites in the Jiangda-Weixi Region, Eastern Tibet: Implications for the Tectonic Evolution of the Paleo-Tethyan Orogen - Rui Gao; Tao Wu; Andrew C. Kerr; Han Liu; Long Xiao; Wan Huang (Journal of Earth Science, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

A single N-rich covalent organic framework-based sensor for electrochemical sensing of 2,4,6-trichlorophenol - Wei-Long Shan; Qian Lu; Heng-Ye Li; Zhong-Xia Wang; Rui Zhang; Mei-Jie Wei; Fen-Ying Kong; Wei Wang (Food Chemistry, 2025)

The effect of microplastic pollution on rice growth, paddy soil properties, and greenhouse gas emissions: A global meta-analysis - Shi-Wen Deng; Wei Liang; Hong-Yu Chen; Mutaz Mohammed Abdallah; Rui-Long Wang (Environmental Research, 2025)

Molecular insights into the adsorption behavior of PFAS on montmorillonite, polyethylene, and polypropylene: A molecular dynamics study - Qiao Wang; Rui Xu; Fusheng Zha; Long Xu; Bo Kang; Heming Han (Computers and Geotechnics, 2025)

Entropy-phase synergy enables stable and high-rate layered oxide cathodes for sodium-ion batteries - Xingyue Yang; Mengfei Du; Jiali Fu; Yi Yang; Zhuo Xiong; Weiyue Li; Liangzhi Li; Jianping Long; Rui Li; Jian Chen; Anjun Hu (Chemical Engineering Journal, 2025)

Self-sustaining one-step synergy of ultrasound-enzyme-ethanol for high-efficiency saponin production from waste Xanthoceras sorbifolium leaves - Huan Long; Rui Guo; Wangsheng Zhu; Fuliang Cao; Erzheng Su; Jiahong Wang (Biomass and Bioenergy, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Calcium and molybdenum isotopes trace eclogitic crust recycling in formation of unique carbonatite-hosted Mo-REE-U-Nb deposits in orogenic belt - Li Tang; Tao Zeng; Thomas Wagner; Tobias Fusswinkel; Long-Long Chen; Jie Li; Rui Wang (Earth and Planetary Science Letters, 2025)

Recent advances in nanomaterial biosensors for the detection of antibiotics to ensure food safety - Bo Long; Qian Zhang; Lintong Zhang; Qiongqiong Xing; Qi Liu; Liying Deng; Fangfang Qu; Rui You; Xuan Wei; Dapeng Ye; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

New point mutations in osmosensing two-component histidine kinase gene associated with iprodione resistance in Monilinia fructicola field isolates from China - Qian Long; Yiyi Guo; Miaomiao Yi; Changsheng Lu; Rui Zhong; Hao Zhang; Usama Amin; Dufang Ke; Zongwen Wang; Fengping Chen (Pesticide Biochemistry and Physiology, 2025)

Transglutaminase-enhanced walnut protein isolate gels: Synergistic effects of double modification on gelation and riboflavin encapsulation - Mengxin Wang; Rui Chen; Long Wu; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Temporal and spatial feature extraction using graph neural networks for multi-point water quality prediction in river network areas - Hang Wan; Long Xiang; Yanpeng Cai; Yulei Xie; Rui Xu (Water Research, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Selective sulfite activation based on a non-radical reaction pathway with dominant 1O2 generation triggered by oxygen vacancies-enriched CuCo2O4 for efficient degradation of ciprofloxacin - Jinyuan Zhang; Long Cao; Jianxin Liu; Yawen Wang; Rui Li; Xiaochao Zhang; Yunfang Wang; Caimei Fan (Journal of Environmental Chemical Engineering, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Recent advancements in chemometrics based non-destructive analytical techniques for rapid detection of adulterants in milk and dairy products – A review - Rui Xu; Muhammad Zeeshan Adil; Sidra Jabeen; Khansa; Mahwish Tanveer; Sadia Younis; Bakhtawar Shafique; Long Li (Food Control, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Desensitization of HMX crystals by formation of co-particles with insensitive LLM-105 or FOX-7 - Zhi-Hua Xue; Yiran Zhang; Rui Pu; Ruixuan Xu; Shuang Li; Qi-Long Yan (Chemical Engineering Journal, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Zircon and apatite constraints on the key factors controlling porphyry Mo mineralization in the Shijiawan deposit: Implication for Mo metallogeny in the Qinling Orogenic Belt - Long-Long Chen; Li Tang; Peng-Rui Lv; Ya-Peng Chen; Tao Zeng (Lithos, 2025)

Wastewater surveillance for chronic disease drugs in wastewater treatment plants: Mass load, removal, and sewage epidemiology - Li Yao; Yang Hu; Jia-Hui Yang; Rui Wu; Fei-Long Chen; Xi Zhou (Journal of Hazardous Materials, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Ensemble framework for multistep carbon emission prediction: an improved Bi-LSTM model based on the Bayesian optimization algorithm and two-stage decomposition - Qi Song; Yu-Long Bai; Rui Wang; Xiao-Xin Yue; Wen-Hui Liu (Stochastic Environmental Research and Risk Assessment, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

Insights into the Rhizosphere and Non-Rhizosphere Phosphorus Bioavailability and Plant Responses Under Molybdenum Supply - Muhammad Shoaib Rana; Rui-Long Wang; Muhammad Imran; Yousif Abdelrahman Yousif Abdellah; Muhammad Riaz; Cheng-xiao Hu (Journal of Soil Science and Plant Nutrition, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

A density-point network for dense tiny stored grain pest counting - Runsheng Qi; Rui Li; Jie Zhang; Yi Xia; Jianming Du; Jiahui Sun; Long chen; Chengjun Xie; Hui Zhang; Guangyu Li (Journal of Stored Products Research, 2025)

Combining the bridging effect of tannic acid and solution activation for improving the lithium/magnesium separation performance of nanofiltration membrane - Tian Wang; Yajiao Long; Rui Yu; Yanqi Gan; Haonan Zhang; Jiahe Li; Mengqi Shi (Desalination, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

A mammary gland secretion function exploratory study based on a quantitative comparison between milk and serum - Li long Wei; Rui Xiao; Yun Zhou; Cheng wu Han; Yong tong Cao (Molecular and Cellular Biochemistry, 2025)

Potential of smartphone-based photogrammetry for measuring particle size and shape in field surveys - Pengju An; Rui Yong; Shigui Du; Yi Long; Jiannan Chen; Zhen Zhong; Kun Fang; Changshuo Wang; Jiamin Song (Bulletin of Engineering Geology and the Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effect of 1-nitropyrene exposure on the biological behavior of trophoblast cells - Chuting Wang; Long Zhang; Daidi Gui; Wenjing Zou; Menglei Zhu; Yu Liu; Lei Hua; Changlian Li; Rui Ding (Reproductive Toxicology, 2025)

Efficient degradation of norfloxacin by ZnCo2O4/halloysite composite activating peroxymonosulfate: Performance and mechanism insights - Long Zhang; Rui Li; Bohao Liu; Yubo Wang; Qingbin Guo; Junying Song; Xiongbo Dong; Li Wang; Xiaolong Hu; Dengzheng Gao (Journal of Water Process Engineering, 2025)

A novel tannic acid/iron/hydrophilic polymer nanofiltration membrane for small organic pollutant/salt separation - Yajiao Long; Yanqi Gan; Xiong Yao; Tian Wang; Haonan Zhang; Rui Yu; Jiahe Li; Mengqi Shi (Journal of Environmental Chemical Engineering, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

Immune cell traits and causal relationships with cholecystitis: a mendelian randomization analysis - Ze-fa Xiao; Wei-hao Chai; Xiao-long Shu; Hong-rui Yuan; Fei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Curcumin protects rat endplate chondrocytes against IL-1β-induced apoptosis via Bcl-2/Bax regulation - Chao Wan; Shixing Liu; Long Zhao; Chengbing Chang; Hewen Li; Rui Li; Bin Chen (Journal of Molecular Histology, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Centrifuge test study on the influence mechanism of anchor cable installation on the seismic response of pile‒anchor structures - Yu Wang; Tong Zheng; Rui Sun; Qiangqiang Sun; Xiao Long; Hongshuai Liu; Wenhao Qi (Soil Dynamics and Earthquake Engineering, 2025)

Description of three new species of Trigonidiidae Saussure, 1874 from China (Orthoptera: Grylloidea) - Tao Li-Long; Yang Rui-Ying; He Zhi-Xin; Ma Li-Bin (Journal of Asia-Pacific Entomology, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Optimizing sowing date to enhance grain yield and quality formation of colored rice in tropical regions of China - Shaokun Song; Rui Yue; Long Chen; Song Li; Ye Tao; Zhenxiang Zhou; Lixiao Nie (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Petrogenesis of the > 2.90 Ga komatiite in the Sujiagou region of the North China Craton: Implications for Archean mantle source and geodynamic setting - Rui Zuo; Xiaoping Long; Bin Wu; Mei-Fu Zhou (Precambrian Research, 2025)

A time series CGAN denoising model targeting vessel’s radiated noise for underwater acoustic communications - Weiliang Tao; Yan Liu; Rui Long; Lei Cheng (Ocean Engineering, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Microplastic effects on soil nitrogen cycling enzymes: A global meta-analysis of environmental and edaphic factors - Yangzhou Xiang; Bin Yao; Josep Peñuelas; Jordi Sardans; Luca Nizzetto; Rui Li; Ying Liu; Yang Luo; Mari Räty; Jian Long; Yuan Li (Journal of Hazardous Materials, 2025)

Piezoelectric polarization-induced photogenerated carriers transfer coupled with active electron transport Z-scheme heterojunction synergistic optimization of BiFeO3/CdS composite photocatalysts for hydrogen production - Xinyu Ma; Rui Li; Zhao Li; Long Zhang; Yongjie Cao; Kui Nie; Die Zhou; Qing Ji; Cheng Wang; Zehua Zhang; Yutian Li; Meidan Que; et al. (Journal of Environmental Chemical Engineering, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Diselenide bond-stapled β-hairpin peptide-loaded hydrogel system for boosting oncolytic immunotherapy - Shengxin Lu; Xiaokun Zhang; Jiayi Lin; Rui Liang; Yiting Gong; Long Gao; Aoyu Cheng; Xinchen Lu; Hongzhuan Chen; Ye Wu; Weidong Zhang; Xin Luan (Chemical Engineering Journal, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Grevillosides R-S: glucosides of 5-alkylresorcinol derivatives from roots of Ardisia crispa (Thunb.) A. DC - Xing-xiang Long; Shuang Zhang; Li-juan Xiang; Rui-hang Hu; Ting-ting Feng; Ying Zhou; Xin Yin (Natural Product Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

Post-modification of covalent organic framework functionalized aminated carbon nanotubes with active site (Fe) for the sensitive detection of luteolin - Ze-Qi Wei; Wei-Long Shan; Lei Li; Heng-Ye Li; Rui Zhang; Juan-Juan Gao; Zhong-Xia Wang; Fen-Ying Kong; Mei-Jie Wei; Wei Wang (Food Chemistry, 2025)

Differential accumulation of bioactive compounds in different populations of Mesona chinensis Benth: An integrated transcriptomic and metabolomic analysis - Yan Qin; Rui Xie; Shirui Peng; Guoming Yang; Xiaomu Yang; Zihao Long; Ying Zheng; Guoli Ye; Minghua Gu; Yanyan Wei (Food Bioscience, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Encapsulation of phase change materials in conjugated microporous polymers hollow microspheres for continuous solar-driven seawater desalination - Yanju Jing; Yong Long; Yiwan Si; Jiyan Li; Hanxue Sun; Rui Jiao; Zhaoqi Zhu; Weidong Liang; An Li (Chemical Engineering Journal, 2025)

Molecular level modulation of anthracite-based hard carbon precursors for efficient sodium-ion batteries - Rui Li; Chunbo Su; Wei Yang; Ruizhe Xu; Kai Chen; Jian Chen; Wei Su; Beilei Yuan; Jianping Long; Anjun Hu (Chemical Engineering Journal, 2025)

Secular evolution of continental crust of the North China Craton constrained by U-Pb and Lu-Hf-O/Sm-Nd isotopic analyses of detrital zircon and monazite in river sediments - Guangyan Zhou; D. Graham Pearson; Yan Luo; Long Li; Christopher M. Fisher; Rui Li; Wei Wang; Yuanbao Wu (Chemical Geology, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Intercropping: ecosystem functioning and sustainable agriculture - Rui-Peng Yu; Dorte B. Dresbøll; Maria R. Finckh; Eric Justes; Wopke van der Werf; Andrew Fletcher; Georg Carlsson; Long Li (Plant and Soil, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Enhancing direct air carbon capture into microalgae: A membrane sparger design with carbonic anhydrase integration - Rui-Long Wang; Ming-Jia Li; Gregory J.O. Martin; Sandra E. Kentish (Algal Research, 2025)

Halobacillus rhizosphaerae sp. nov., a moderately halophilic bacterium with protease activities isolated from the rhizosphere soil of the mangrove Acanthus ebracteatus - Doudou Yin; Junjie Xie; Rui Liu; Chaodong Song; Ying Liang; Hongzhi Huang; Yihui Huang; Ruiting Long; Naikun Shen; Bing Yan; Hongyan Zhang (Antonie van Leeuwenhoek, 2025)

Tools in Harmony: Integrating Observations and Models for Improved Understanding of a Changing Ocean - Erica Ombres; Heather Benway; Kelsey Bisson; Alyse Larkin; Elizabeth Perotti; Elizabeth Wright-Fairbanks; Joey Crosswell; Sandupal Dutta; Cynthia Garcia; Anand Gnanadesikan; Kalina Grabb; Amanda Fay; et al. (Oceanography, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Nonfragile memory-based sampled-data control for Unmanned Surface Vehicles with time-varying coupling delay - Xinyuan Long; Hua Chen; Jinhai Zheng; Jisheng Zhang; Mi-An Xue; Yao Tang; Rui Xu; Yang Zhao (Ocean Engineering, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Comparative study of pre- and post-Cu modified calcium-based desulfurizers: Experimental and theoretical insights into adsorption vs. catalysis - Xiaodong Liao; Yulu Liu; Zongshe Liu; Qisong Liu; Wanglai Cen; Rui Fan; Long Li; Jing Shao; Yuxiao Shi (Journal of Environmental Chemical Engineering, 2024)

Highly selective separation of 99TcO4−/ReO4− with rapid liquid-liquid two-phase disengagement by amine-diamide ligands - Long Li; Xuanhao Huang; Xiaoyang Hu; Xingyue Liu; Rui Li; Hang Zhou; Fengfeng Li; Fangxiang Luo; Qingjiang Pan; Songdong Ding (Journal of Environmental Chemical Engineering, 2024)

Astragaloside IV alleviates diabetic nephropathy by modulating the gut-kidney axis and AMPK/PI3K/AKT pathway - Pin Gong; Hui Long; Qian Yang; Rui Zhou; Wenjuan Yang; Fuxin Chen; Jianwu Xie; Yanni Zhao; Hongbo Xu (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Clinical significance and potential mechanism of hsa_circ_0006892 in acute respiratory distress syndrome complicated with pulmonary fibrosis - Shuping Zhang; Lingbo Rong; Guangwen Long; Feihong Huang; Qian Zhang; Xiulin Yang; Hongpeng Sun; Chunling Ji; Rui-hai Ye (Molecular Biology Reports, 2024)

Imitation expansion bolts structural bonding interface: Enhancing the bonding properties of bamboo composites through host–guest molecular recognition - Rui Zhao; Tongda Liu; Xin Ran; Jun Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2024)

The role and function mechanism of tapP in modulating the virulence of Aeromonas hydrophila - Rui Long; Jinming Wei; Caijiang Xiong; Bei Wang; Jiahui Lu; Hua Ye; Yun Li; Yongyao Yu; Lingyun Lin; Ronghua Wu (Aquaculture, 2024)

A bifunctional amylopullulanase of Streptococcus suis ApuA contributes to immune evasion by interaction with host complement C3b - Jiajia Xu; Jiaqi Zhu; Weiyao Han; Siqi Pang; Simin Deng; Long Chen; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2024)

New data on Silurian (Llandovery) sinacanthids from Wuhan, South China and their biostratigraphic and paleobiogeographic implications - Yi-Long Liu; Jia-Yi Yin; Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Discovery of the earliest Devonian conodonts from Xinjiang, Northwest China - Jia-Yi Yin; Ladislav Slavík; Jian-Feng Lu; Juan Ma; Yi-Long Liu; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Quantitative evaluation method for post-earthquake functionality loss of pedestrian flow pathways within a complex building using evacuation and rescue simulation - Zhao-Long Shi; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Han Zhang; Rui Wang (Engineering Structures, 2024)

General synthesis of porous metal oxides nanosheets for gas sensing by gradient crystallization induced spatial confinement approach - Xuan-Yu Yang; Rui-Jie Zhao; Fei-Long Gong; Ke-Feng Xie; Hua Xu; Yong-Hui Zhang (Chemical Engineering Journal, 2024)

Molecularly engineered chitosan-derived poly(aprotic/protic ionic liquids) double-network hydrogel electrolytes for flexible supercapacitors and wearable strain sensors - Hailiang Sheng; Rongli Li; Rui Li; Long Li; Shizhao Li; Yunqi Li; Jili Yuan; Jun Huang; Qinqin Xu; Qiang Zheng; Lihua Zhang; Haibo Xie (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Hybrid neural network wind speed prediction based on two-level decomposition and weighted averaging - Qi Bi; Yu-long Bai; Zai-hong Hou; Rui Wang (Earth Science Informatics, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

First complete Niobe yangtzeensis Lu, 1975 (Asaphidae, Trilobita) from the Middle Ordovician of South China, and its systematic and palaeogeographic implications - Xiao-Qi Du; Yi-Long Liu; Rui-Wen Zong (Palaeoworld, 2024)

Particle size shapes prokaryotic communities and vertical connectivity in the water columns of the slope and central basin of the South China Sea - Zhonglin Ma; Paraskevi Mara; Lei Su; Long Wang; Huifang Li; Rui Zhang; Virginia P. Edgcomb; Jiangtao Li (Global and Planetary Change, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

The Roles of Non-coding RNA Targeting Astrocytes in Cerebral Ischemia - Chun-mei Long; Zhen Li; Wang Song; Xin Zeng; Rui Yang; Li Lu (Molecular Neurobiology, 2024)

Development and characterization of a bacterial enzyme cascade reaction system for efficient and stable PET degradation - Chengyong Wang; Rui Long; Xiran Lin; Wei Liu; Liying Zhu; Ling Jiang (Journal of Hazardous Materials, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Vernalization promotes bolting in sugar beet by inhibiting the transcriptional repressors of BvGI - Chunxue Zhang; Shengnan Li; Yuguang Wang; Jiali Long; Xinru Li; Lixun Ke; Rui Xu; Zedong Wu; Zhi Pi (Plant Molecular Biology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Non-fragile control associated with exponential stability for unmanned surface vessels with the rudder failure and dynamic event-trigger - Xinyuan Long; Hua Chen; Jinhai Zheng; Mi-An Xue; Rui Xu; Yao Tang; Yang Zhao (Ocean Engineering, 2024)

Origin of mafic microgranular enclaves from the Late Triassic Cuojiaoma granitic pluton: Implications for the tectonic evolution of the Yidun arc belt, eastern Tibetan Plateau - Rui Gao; Tao Wu; Andrew C. Kerr; Long Xiao (Journal of Asian Earth Sciences, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Synergistic enhancement of phase change materials through three-dimensional porous layered covalent triazine framework/expanded graphite composites for solar energy storage and beyond - Long Geng; Jiapeng Wang; Xulong Yang; Jiaping Jiang; Rui Li; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Trifluoperazine activates AMPK / mTOR / ULK1 signaling pathway to induce mitophagy in osteosarcoma cells - Wenhui Shen; Xiangchen Zeng; Xianhui Zeng; Baoshan Hu; Chong Ren; Zhiming Lin; Long Zhang; Gang Rui; Miersalijiang Yasen; Xiaohui Chen (Chemico-Biological Interactions, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Numerical Simulation of the Mass Movement Process of the 2018 Sedongpu Glacial Debris Flow by Using the Fluid-Solid Coupling Method - Xing-Yu Long; Yu-Xiang Hu; Bin-Rui Gan; Jia-Wen Zhou (Journal of Earth Science, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

Characterization of potassium-solubilizing fungi, Mortierella spp., isolated from a poplar plantation rhizosphere soil - Rui Zhu; Long Jin; Yue Sang; Shuang Hu; Bao-Teng Wang; Feng-Jie Jin (Archives of Microbiology, 2024)

Topological spin-orbit-coupled fermions beyond rotating wave approximation - Han Zhang; Wen-Wei Wang; Chang Qiao; Long Zhang; Ming-Cheng Liang; Rui Wu; Xu-Jie Wang; Xiong-Jun Liu; Xibo Zhang (Science Bulletin, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Study on the mechanism of Panax notoginseng–Salvia miltiorrhiza herb pair on invigorating blood circulation and eliminating blood stasis by blocking the conversion of arachidonic acid to prostaglandin - Rui Zeng; Yuefan Zhang; Shengtong Shi; Xianqin Long; Haixia Zhang; Min Wang; Jianfeng Shi; Ye Jiang; Bin Chen (Journal of Natural Medicines, 2024)

The residues and health risk assessment of polychlorinated biphenyls (PCBs) in Pheretima (an earthworm-derived traditional medicine) from southeastern China - Yun-Jing Zhang; Jing Sun; Xiao-Jiang Chen; Rui Cheng; Zhi-Tong Liu; Ling Cao; You-Long Feng (Environmental Science and Pollution Research, 2024)

Stereoselective cardiotoxic effects of metconazole on zebrafish (Danio rerio) based on AGE-RAGE signalling pathway - Minmin Li; Lin Yang; Rui Wang; Lin Li; Yifan Zhang; Long Li; Nuo Jin; Yatao Huang; Zhiqiang Kong; Frédéric Francis; Bei Fan; Fengzhong Wang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Shaking table test and numerical simulation of a precast frame-shear wall structure with innovative untopped precast concrete floors - Rui Pang; Yuan-yuan Sun; Zhu Xu; Ke Xu; Jing Cui; Long-ji Dang (Engineering Structures, 2024)

Responses of carbon and microbial community structure to soil nitrogen status vary between maize and potato residue decomposition - Linkang Chen; Ping Zhao; Chunyan Ming; Wenchun Yu; Rui Xiang; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Imperfect but effective crypsis and flower-visiting strategy in a crab spider - Zichang Li; Long Yu; Guocheng Yu; Rui Zhong; Yao Zhao; Jie Liu; Yu Peng (Behavioral Ecology and Sociobiology, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Effects of root rot on microbial communities associated with goji berry (Lycium barbarum) in the Qaidam Basin, China - Zhilin Feng; Yuancan Xiao; Na Li; Qingbo Gao; Jiuli Wang; Shi-long Chen; Rui Xing (European Journal of Plant Pathology, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Manipulation of crystallization nucleation and thermal degradation of PLA films by multi-morphologies CNC-ZnO nanoparticles - Ya-Fang Yan; Xiao-Bo Liang; Yan-Long Feng; Lin-Fang Shi; Rui-Pin Chen; Jian-Zhong Guo; Ying Guan (Carbohydrate Polymers, 2023)

Adsorption Optimization of Methylene Blue from Aqueous Solution by Cost-Effective Biochar Using Response Surface Methodology and a Modeling Approach - Rui Duan; Yongchun Chen; Yuzhi Zhou; Linli Long; Zhiyang Jiang; Xiaoyang Chen (Water, Air, & Soil Pollution, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

A new modified pterocarpan glycoside from Sophora flavescens - Yan Lin; Jing-Jing Li; Lei He; Qi-Rui Li; Qing-De Long; Xu Zhang; Zhu Zeng (Natural Product Research, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

A novel calcium peroxide/attapulgite-Fe(II) process for high concentration phosphate removal and recovery: Efficiency and mechanism - Jun Luo; Jia Peng; Zhenxing Zhong; Xuejun Long; Jiazhi Yang; Rui Li; Jun Wan (Journal of Environmental Management, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Reducing carbon footprints and increasing net ecosystem economic benefits through dense planting with less nitrogen in double-cropping rice systems - Wentao Zhou; Wenfei Long; Hongrui Wang; Pan Long; Ying Xu; Kangyu Zhong; Rui Xiong; Feipeng Xie; Fugui Chen; Zhiqiang Fu (Science of The Total Environment, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Transient analyses for China initiative Accelerator Driven System using the extended BELLA code - Guan Wang; Janne Wallenius; Rui Yu; Wei Jiang; Lu Zhang; Xin Sheng; Di Yun; Long Gu (Annals of Nuclear Energy, 2023)

Quality assurance and quality control throughout microplastic analysis - Long Zhu; Yanyan Yu; Jingying Zhu; Rui Zuo; Qiujin Xu; Lihui An; Yanhua Qian (Science of The Total Environment, 2023)

First occurrence of caryocaridids (Crustacea, Phyllocarida) in the Ordovician of North China - Yi-long Liu; Ruo-ying Fan; Rui-wen Zong; Yi-ming Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

A ZSG-DEA model with factor constraint cone-based decoupling analysis for household CO2 emissions: a case study on Sichuan province - Rui Zhao; Jie Liu; Hai Long; Xin Xiong; Dingye Wu (Environmental Science and Pollution Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

Correction to: Mitochondrial Hydrogen Peroxide Activates PTEN and Inactivates Akt Leading to Autophagy Inhibition-Dependent Cell Death in Neuronal Models of Parkinson’s Disease - Qianyun Yu; Ruijie Zhang; Tianjing Li; Liu Yang; Zhihan Zhou; Long Hou; Wen Wu; Rui Zhao; Xiaoling Chen; Yajie Yao; Shile Huang; Long Chen (Molecular Neurobiology, 2023)

Gold endowment and unloading along pathway for giant gold mineralization: Insights from spatiotemporal variations of in-situ pyrite geochemistry and gold fineness from the Jiaodong gold deposits, north China Craton - Ting-Guang Lan; Hong Wang; Hong-Rui Fan; Thomas Ulrich; Huan-Long Hu; You-Wei Chen; Lei Shu (Gondwana Research, 2023)

Recent advances on the preparation and combustion performances of boron-based alloy fuels - Danfeng Yang; Rui Liu; Wei Li; Qi-Long Yan (Fuel, 2023)

Mitochondrial Hydrogen Peroxide Activates PTEN and Inactivates Akt Leading to Autophagy Inhibition-Dependent Cell Death in Neuronal Models of Parkinson’s Disease - Qianyun Yu; Ruijie Zhang; Tianjing Li; Liu Yang; Zhihan Zhou; Long Hou; Wen Wu; Rui Zhao; Xiaoling Chen; Yajie Yao; Shile Huang; Long Chen (Molecular Neurobiology, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

EphA1 aggravates neuropathic pain by activating CXCR4/RhoA/ROCK2 pathway in mice - Qi Li; Rui Li; Xiaoxi Zhu; Xiaolei Chu; Xiaoqiong An; Ming Chen; Lei Zhang; Mingwei Gao; Long Chen (Human Cell, 2023)

A testis-specific gene doublesex is involved in spermatogenesis and early sex differentiation of the Chinese mitten crab Eriocheir sinensis - Long Wang; Zhi-Qiang Liu; Ke-Yi Ma; Jing-Rui Tao; Xiang Fang; Gao-Feng Qiu (Aquaculture, 2023)

Plant litter strengthens positive biodiversity–ecosystem functioning relationships over time - Wei-Ping Zhang; Dario Fornara; Hao Yang; Rui-Peng Yu; Ragan M. Callaway; Long Li (Trends in Ecology & Evolution, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Cl modulation on boron-rich carbon embedded with NiFe alloys for efficient oxygen evolution reaction - Jiateng Li; Kaitian Zheng; Chi Zhang; Long Jiao; Zhiheng Dong; Xinyue Tao; Rui Su; Haijiao Xie; Chunjian Xu (Chemical Engineering Journal, 2023)

Fluid evolution and ore genesis of the Tiantangshan granite-related vein-type Rb-Sn-W deposit, south China: constraints from LA-ICP-MS analyses of fluid inclusions - Hong-Wei Peng; Hong-Rui Fan; Pilar Lecumberri-Sanchez; Jian-Qing Lai; Huan-Long Hu; Ting-Guang Lan; Xing-Hui Li (Mineralium Deposita, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Upcycling corn straw into nanocelluloses via enzyme-assisted homogenization: Application as building blocks for high-performance films - Hongbin Yang; Long Bai; Yaxin Duan; Hongxiang Xie; Xumei Wang; Rui Zhang; Xingxiang Ji; Chuanling Si (Journal of Cleaner Production, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Experimental and numerical study on axial compressive behaviors of reinforced UHPC-CFST composite columns - Xiao-Long Gao; Shi-Yu Shen; Gui-Xiang Chen; Rui Pang; Min Mao (Engineering Structures, 2023)

Sulfite altered permanganate effects on acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Lijuan Wu; Rui Zhu; Xiaoxia Han; Yan Chen; Zhen Long; Hao Dong; Xiaojiang Chen; Yang Wu; Yinglong Su; Zhengyong Zhang; Jingyang Luo (Bioresource Technology, 2023)

Experimental study on the effects of salt solution pH on the performance of reverse electrodialysis stack - Lu Wang; Yanan Zhao; Xi Chen; Rui long; Zhichun Liu; Wei Liu (Process Safety and Environmental Protection, 2023)

Breakage-resistant hydrogel electrode enables ultrahigh mechanical reliability for triboelectric nanogenerators - Rui Li; Zhenyu Xu; Long Li; Junjie Wei; Wenqin Wang; Zejun Yan; Tao Chen (Chemical Engineering Journal, 2023)

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Identification of microplastics in human placenta using laser direct infrared spectroscopy - Long Zhu; Jingying Zhu; Rui Zuo; Qiujin Xu; Yanhua Qian; Lihui AN (Science of The Total Environment, 2023)

OsHLS1 regulates plant height and development by controlling active gibberellin accumulation in rice (Oryza sativa L.) - Tonghua Zhang; Jiafu Wang; Rui Luo; Jianmin Man; Qing Long; Ning Xu (Plant Science, 2023)

Proterozoic mantle melting recorded by the Re-Os isotopic systematics of ophiolites from the Qilian Orogenic Belt, northwestern China - Jing Zhao; Qianru Xiao; Yilin Gao; Rui Zuo; Luyu Huang; Jie Li; Xiaoping Long (Journal of Asian Earth Sciences, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

A new method for retrieving urban heat island intensity using GNSS-derived ZTD and atmospheric empirical model - Qimin He; Li Li; Dajun Lian; Hang Yu; Guodong Chen; Biqing Gao; Rui Wang; Kangming Song; Long Li (International Journal of Remote Sensing, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Cardiac Expression of Esophageal Cancer-Related Gene-4 is Regulated by Sp1 and is a Potential Early Target of Doxorubicin-Induced Cardiotoxicity - Dandan Long; Chunyue Chen; Wei Li; Wanling Peng; Dongmei Li; Rui Zhou; Xitong Dang (Cardiovascular Toxicology, 2022)

Influence of combined exposure levels of total arsenic and inorganic arsenic on arsenic methylation capacity among university students: findings from Bayesian kernel machine regression analysis - Rui Jiang; Qing Zhang; Dongmei Ji; Tingting Jiang; Yuan Hu; Shitao He; Long Tao; Juan Shen; Wei Zhang; Yuxiang Song; Yicheng Ma; Shilu Tong; et al. (Environmental Science and Pollution Research, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

GIS-based spatial prediction of landslide using road factors and random forest for Sichuan-Tibet Highway - Cheng-ming Ye; Rui-long Wei; Yong-gang Ge; Yao Li; José Marcato Junior; Jonathan Li (Journal of Mountain Science, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Picraquanines A－C, three new phenolic derivatives from the stems of Picrasma quassioides - Rui Xu; Dongdong Zhang; Fangfang Shu; Zehai Long; Yiming Li; Zhengtao Wang; Li Yang; Rui Wang (Natural Product Research, 2021)

Globular adiponectin inhibits osteoblastic differentiation of vascular smooth muscle cells through the PI3K/AKT and Wnt/β-catenin pathway - Yun Zhou; Li-Long Wei; Rui-Ping Zhang; Cheng-Wu Han; Yongtong Cao (Journal of Molecular Histology, 2021)
Lipid metabolism is closely related to the improvement of vascular calcification (VC) in chronic kidney disease (CKD). Globular adiponectin (gAd) has been reported to be involved in the development of VC in CKD, but the detailed regulatory role remains unclear. The present study is aimed to investigate the biological function and the underlying regulation mechanism of gAd in the process of VC during CKD. Vascular smooth muscle cells (VSMCs) calcification was determined by Alizarin Red S staining. Protein signaling related with VC was tested by western blotting. The expression and intracellular localization of runt-related transcription factor 2 (Runx2) was detected by immunofluorescence and uraemic rat with VC was established by a two-step nephrectomy. Combined with the results of Alizarin Red S staining, we discovered that β-glycerophosphate (β-Gp)-induced the osteoblastic differentiation of VSMCs was significantly reversed by gAd treatment. Along with the VSMCs calcification and the increase of Runx2 in β-Gp-exposed VSMCs, the activities of protein kinase B (AKT) and Wnt/β-catenin pathway were enhanced, but that were counteracted by the exposure of gAd in rat and human VSMCs. After administration with agonists of the Wnt (SKL2001) and AKT (SC79), there appeared more osteoblastic differentiation and higher expression of Runx2 in gAd-treated VSMCs, but showing lower impact in the presence of SC79 than that in the presence of SKL2001. In the in vivo experiments, intravenous injection of gAd also significantly inhibited VC and Runx2 level in uraemic rat in a dose-dependent manner, possibly through regulating Wnt/β-catenin pathway. This study demonstrates that gAd ameliorates osteoblastic differentiation of VSMCs possibly by blocking PI3K/AKT and Wnt/β-catenin signaling transduction. The findings provide an important foundation for gAd in treating VC in kidney diseases.

Damage evolution of phyllite based on uniaxial compression and acoustic emission tests - Rui Wang; Chenke Sun; Xianghui Deng; Yuncai Wang; Kai Long (Arabian Journal of Geosciences, 2021)

Numerical Investigation of the Characteristics of Erosion in a Centrifugal Pump for Transporting Dilute Particle-Laden Flows - Rui-Jie Zhao; You-Long Zhao; De-Sheng Zhang; Yan Li; Lin-Lin Geng (Journal of Marine Science and Engineering, 2021)
Erosion in centrifugal pumps for transporting flows with dilute particles is a main pump failure problem in many engineering processes. A numerical model combining the computational fluid dynamics (CFD) and Discrete Element Method (DEM) is applied to simulate erosion in a centrifugal pump. Different models of the liquid-solid inter-phase forces are implemented, and the particle-turbulence interaction is also defined. The inertial particles considered in this work are monodisperse and have finite size. The numerical results are validated by comparing the results with a series of experimental data. Then, the effects of particle volume fraction, size, and shape on the pump erosion are estimated in the simulations. The results demonstrate that severe erosive areas are located near the inlet and outlet of the pressure side of the impeller blade, the middle region of the blade, the corners of the shroud and hub of the impeller adjoining to the pressure side of the blade, and the volute near the pump tongue. Among these locations, the maximum erosion occurs near the inlet of the pressure side of the blade. Erosion mitigation occurs under the situation where more particles accumulate in the near-wall region of the eroded surface, forming a buffering layer. The relationship between the particle size and the erosion is nonlinear, and the 1 mm particle causes the maximum pump erosion. The sharp particles cause more severe erosion in the pump because both the frequency of particle-wall collisions and the impact angle increase with the increasing sharpness of the particle.

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Distinctive distributions of halophilic Archaea across hypersaline environments within the Qaidam Basin of China - Derui Zhu; Guoping Shen; Zhibo Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Yongzhen Li; Rong Wang (Archives of Microbiology, 2021)

A novel reverse circulation drilling device for the underground sampling to soft coal - Xianshang Zhang; Qingming Long; Zheming Zhu; Meng Wang; Rui Zhang; Deming Chen; Jiangong Li (Arabian Journal of Geosciences, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

The resurgent landscape of xenotransplantation of pig organs in nonhuman primates - Xuan Zhang; Quancheng Wang; Jingjun Zhao; Xiao Li; Wei Peng; Zhaoxu Yang; Zhibin Lin; Long Yang; Rui Ding; Kaishan Tao; Kefeng Dou (Science China Life Sciences, 2021)

Nitrogen fertilization overweighs intercropping in promotion of dissolved organic carbon concentration and complexity in potato-cropped soil - Ding Wang; Ping Zhao; Rui Xiang; Shuran He; Yanli Zhou; Xinhua Yin; Guangqiang Long (Plant and Soil, 2021)

Experimental and numerical study on the fragmentation mechanism of a single calcareous sand particle under normal compression - Du-min Kuang; Zhi-lin Long; Rui-qi Guo; Tao Zhao; Kai Wu (Bulletin of Engineering Geology and the Environment, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

The circular RNAs differential expression profiles in the metastasis of salivary adenoid cystic carcinoma cells - Rui Ju; Yanling Huang; Zeyou Guo; Lu Han; Suhui Ji; Luyang Zhao; Jie Long (Molecular and Cellular Biochemistry, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

T4 ‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea - Huifang Li; Lu Liu; Yu Wang; Lanlan Cai; Maoqiu He; Long Wang; Chen Hu; Nianzhi Jiao; Rui Zhang (Environmental Microbiology, 2021)
Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operational taxonomic units were affiliated with previously defined Marine, Estuary, Lake and Paddy Groups. A clear viral biogeographic pattern was observed along the environmental gradient from the estuary to open sea. Marine Groups I and IV had a wide geographical distribution, whereas Marine Groups II, III and V were abundant in lower‐salinity continental or eutrophic environments. A significant distance‐decay pattern was noted for the T4‐like viral community, especially for those infecting cyanobacteria. Both deterministic and dispersal processes influenced viral community assembly, although environmental selection (e.g. temperature, salinity, bacterial abundance and community, etc.) had a greater impact than spatial distance. Network analysis confirmed the strong association between viral and bacterial community composition, and suggested a diverse ecological relationship (e.g. lysis, co‐infection or mutualistic) between and within viruses and their potential bacterial hosts.

Effect of different industrial activities on soil heavy metal pollution, ecological risk, and health risk - Zhijie Long; Yi Huang; Wei Zhang; Zhangliang Shi; Daming Yu; Ying Chen; Chao Liu; Rui Wang (Environmental Monitoring and Assessment, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Bacterial and Archaeal Communities within an Ultraoligotrophic, High-altitude Lake in the Pre-Himalayas of the Qinghai-Tibet Plateau - Rong Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Derui Zhu (Indian Journal of Microbiology, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Evaluation of the Biodiversity Conservation Function in Liaohe Delta Wetland, Northeastern China - Wenying Yu; Ruipeng Ji; Xiuzhen Han; Long Chen; Rui Feng; Jinwen Wu; Yushu Zhang (Journal of Meteorological Research, 2020)

High risk of activation of latent tuberculosis infection in rheumatic disease patients - Wei Long; Fen Cai; Xinyi Wang; Nan Zheng; Rui Wu (Infectious Diseases, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

TGF-β Secretion by M2 Macrophages Induces Glial Scar Formation by Activating Astrocytes In Vitro - Gongyu Song; Rui Yang; Qian Zhang; Long Chen; Dujuan Huang; Junwei Zeng; Changpei Yang; Tao Zhang (Journal of Molecular Neuroscience, 2019)

Changes in bacterial community structure and humic acid composition in response to enhanced extracellular electron transfer process in coastal sediment - Jiulong Zhao; Long Wang; Lili Tang; Rui Ren; Wuxin You; Robina Farooq; Zejie Wang; Yongyu Zhang (Archives of Microbiology, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

ANKRD49 inhibits etoposide-induced intrinsic apoptosis of GC-1 cells by modulating NF-κB signaling - Xia Zhou; Wen-tao Wang; Jia Sun; Hong-yan Liu; Xin-yan Bai; Juan-juan Liu; Bao-feng Yu; Rui Guo; Hai-long Wang (Molecular and Cellular Biochemistry, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Laminar Distribution of Neurochemically-Identified Interneurons and Cellular Co-expression of Molecular Markers in Epileptic Human Cortex - Qiyu Zhu; Wei Ke; Quansheng He; Xiongfei Wang; Rui Zheng; Tianfu Li; Guoming Luan; Yue-Sheng Long; Wei-Ping Liao; Yousheng Shu (Neuroscience Bulletin, 2018)

Augmenter of liver regeneration promotes mitochondrial biogenesis in renal ischemia–reperfusion injury - Li-li Huang; Rui-ting Long; Gui-ping Jiang; Xiao Jiang; Hang Sun; Hui Guo; Xiao-hui Liao (Apoptosis, 2018)

A new isoflavanone from Ficus tikoua Bur - Si-Yu Zhou; Rui Wang; Li-Qing Deng; Xiao-Long Zhang; Min Chen (Natural Product Research, 2018)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Fast 3D forward modeling of the magnetic field and gradient tensor on an undulated surface - Kun Li; Long-Wei Chen; Qing-Rui Chen; Shi-Kun Dai; Qian-Jiang Zhang; Dong-Dong Zhao; Jia-Xuan Ling (Applied Geophysics, 2018)

Transformations of 2-line ferrihydrite and its effect on cadmium adsorption - Yi Huang; Shipeng Zhang; Chao Liu; Huilin Lu; Shijun Ni; Xin Cheng; Zhijie Long; Rui Wang (Environmental Science and Pollution Research, 2018)

Cryobiotechnology of apple (Malus spp.): development, progress and future prospects - Min-Rui Wang; Long Chen; Jaime A. Teixeira da Silva; Gayle M. Volk; Qiao-Chun Wang (Plant Cell Reports, 2018)

A new cinnamic acid glycoside from roots of Heracleum dissectum - Zhi-Gang Wang; Jie Mi; Xin-Rui Wang; Ya-Yu Huo; Ya-Jie Peng; Hai-Min Zhang; Yang Gao; Hai-Long Zhang (Natural Product Research, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Remains of trilobites and other species discovered in a volcanic ash bed of the end-Permian, Yangtze craton, South China - Zejin Shi; Leixun Lu; Guan Yin; Hongyu Long; Wenjie Li; Huaixin Yang; Rui Cao; Xuesong Tian; Qian Tan; Kun Wang; Yong Wang; Yaming Tian (International Geology Review, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

A novel genetic algorithm for optimization of conditioning factors in shallow translational landslides and susceptibility mapping - Long Li; Rui Liu; Saied Pirasteh; Xianhua Chen; Long He; Jonathan Li (Arabian Journal of Geosciences, 2017)

Genotoxicity and cytotoxicity reduction of the polluted urban river after ecological restoration: a field-scale study of Jialu River in northern China - Jie Sun; Rui Zhang; Long Qin; Haixiao Zhu; Yu Huang; Yingang Xue; Shuqing An; Xianchuan Xie; Aimin Li (Environmental Science and Pollution Research, 2017)

Validation of the quantitative trait locus underlying soybean plant height using residual heterozygous lines and near-isogenic lines across multi-environments - Long Yan; Yuanyuan Zhang; Qijian Song; Perry B. Cregan; Chunyan Yang; Yongqiang Charles An; Chengjun Wu; Qiang Chen; Bingqiang Liu; Rui Di; Mengchen Zhang (Euphytica, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Molecular cloning and characterization of the MsHSP17.7 gene from Medicago sativa L. - Zhen-yi Li; Rui-cai Long; Tie-jun Zhang; Qing-chuan Yang; Jun-mei Kang (Molecular Biology Reports, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Magnetic effervescent tablet-assisted ionic liquid dispersive liquid–liquid microextraction of selenium for speciation in foods and beverages - Xiaojun Wang; Long Wu; Jiaqi Cao; Xincheng Hong; Rui Ye; Weiji Chen; Ting Yuan (Food Additives & Contaminants: Part A, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

A Novel Chromone Schiff-Base Fluorescent Chemosensor for Cd(II) Based on C=N Isomerization - Jun Yan; Long Fan; Jing-can Qin; Chao-rui Li; Zheng-yin Yang (Journal of Fluorescence, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

A Chromone-Derived Schiff-Base Ligand as Al3+ “Turn on” Fluorescent Sensor: Synthesis and Spectroscopic Properties - Chao-rui Li; Jing-can Qin; Bao-dui Wang; Long Fan; Jun Yan; Zheng-yin Yang (Journal of Fluorescence, 2016)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Predicting invasions of Wedelia trilobata (L.) Hitchc. with Maxent and GARP models - Zhong Qin; Jia-en Zhang; Antonio DiTommaso; Rui-long Wang; Rui-shan Wu (Journal of Plant Research, 2015)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

A Controlled Study of Alprostadil Liposomal Preparation in the Treatment of Blue Toe Syndrome - Hai-lin Xi; Rui Li; Zhi-long Tian; Su Feng; Gao-Lei Jia (Cell Biochemistry and Biophysics, 2015)

Bencycloquidium bromide inhibits nasal hypersecretion in a rat model of allergic rhinitis - Rui Long; Yuanda Zhou; Jiangju Huang; Li Peng; Long Meng; Shenyin Zhu; Juan Li (Inflammation Research, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Composition and variation analysis of TCR β-chain CDR3 repertoire in the thymus and spleen of MRL/lpr mouse at different ages - Zhou Li; Ma Long; Liu ChunMei; Shi Bin; Yu Jiang; Ma Rui; Ma Qingqing; Yao XinSheng (Immunogenetics, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

Petrogenesis and tectonic setting of the Queershan composite granitic pluton, eastern Tibetan Plateau: Constraints from geochronology, geochemistry and Hf isotope data - Tao Wu; Long Xiao; Rui Gao; HaiJun Yang; Gang Yang (Science China Earth Sciences, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Simultaneous Determination of Calycosin-7-O-β-d-Glucoside, Ononin, Calycosin, Formononetin, Astragaloside IV, and Astragaloside II in Rat Plasma After Oral Administration of Radix Astragali Extraction for Their Pharmacokinetic Studies by Ultra-Pressure Liquid Chromatography with Tandem Mass Spectrometry - Xiao-hua Liu; Jian-bang Zhao; Long Guo; Ying-lai Yang; Fang Hu; Rui-juan Zhu; Shi-lan Feng (Cell Biochemistry and Biophysics, 2014)

Airborne fine particulate matter induces multiple cell death pathways in human lung epithelial cells - Xiaobei Deng; Fang Zhang; Lijuan Wang; Wei Rui; Fang Long; Yong Zhao; Deliang Chen; Wenjun Ding (Apoptosis, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Local responses to macro development policies and their effects on rural system in China’s mountainous regions: the case of Shuanghe Village in Sichuan Province - Yu-rui Li; Yan-sui Liu; Hua-lou Long; Jie-yong Wang (Journal of Mountain Science, 2013)
China has promulgated a series of policies including the Western Development Program, the Grain for Green Project, agricultural support policies and building a new countryside strategy to eliminate east-west differences and urban-rural disparities since the late 1990s. This paper gives a holistic examination on local responses to the four typical macro socio-economic development policies and their effects on rural system based on a case study of a mountainous village in southern Sichuan Province. The results showed that the policies have not moved the case study village from its historically marginal status. To some extent, its socio-economic situation might have been worsened by accelerated out-migration of the youth, loss of agricultural land due to afforestation and industrial plants, increased fire hazard due to afforestation and reforestation, increased environmental pollution due to industrial enterprises attracted to the village and a steep decline in agricultural production due to loss of and inefficient use of cultivated land. Factors causing local villages’ dilemmas include the nonuniformity of actors’ objectives, finiteness of villagers’ abilities, and the imperfect incentive and restraint mechanism for local government’s activities under existing policy framework composed of uncoordinated one-size-fits-all policies. We suggest that China’s rural policy in the new period should gradually shift from a sectoral to a place-based one, from top-down incentives to the development of bottom-up projects, and fully recognize the diversity of rural space, so as to lift local capacities and make good use of the knowledge shared by different actors. Moreover, it is also necessary to integrate the various sectoral policies, and improve the interministerial and interdepartmental coordination of rural policies at regional and local levels.

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

Seed rain and its relationship with above-ground vegetation of degraded Kobresia meadows - Zhan-Huan Shang; Shi-Hai Yang; Jian-Jun Shi; Yan-Long Wang; Rui-Jun Long (Journal of Plant Research, 2013)

Karyotype of asparagus by physical mapping of 45S and 5S rDNA by FISH - CHUAN-LIANG DENG; RUI-YUN QIN; NING-NA WANG; YING CAO; JUN GAO; WU-JUN GAO; LONG-DOU LU (Journal of Genetics, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Combined analysis of the association between p73 G4C14-to-A4T14 polymorphisms and cancer risk - Lan Wang; Rui Gao; Long Yu (Molecular Biology Reports, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Innate and evolutionarily increased advantages of invasive Eupatorium adenophorum over native E. japonicum under ambient and doubled atmospheric CO2 concentrations - Yan Bao Lei; Yu Long Feng; Yu Long Zheng; Rui Fang Wang; He De Gong; Yi Ping Zhang (Biological Invasions, 2011)

Historical and botanical evidence of distribution, cultivation and utilization of Linum usitatissimum L. (flax) in China - Fei-Hu Liu; Xia Chen; Bo Long; Rui-Yan Shuai; Chun-Lin Long (Vegetation History and Archaeobotany, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Changes in soil biochemical properties associated with Ligularia virgaurea spreading in grazed alpine meadows - Xiao Ming Shi; Xiao Gang Li; Rong Mei Wu; Yun Hui Yang; Rui Jun Long (Plant and Soil, 2011)

How Human Household Size Affects the Habitat of Black-and-White Snub-Nosed Monkeys (Rhinopithecus bieti) in Hongla Snow Mountain Nature Reserve in Tibet, China - Rui-Chang Quan; Yong Huang; Matthew W. Warren; Qi-Kun Zhao; Guopeng Ren; Sheng Huo; Yongcheng Long; Jianguo Zhu (International Journal of Primatology, 2011)

The Electrostatic Interactions Between Nano-TiO2 and Trypsin Inhibit the Enzyme Activity and Change the Secondary Structure of Trypsin - Wen-Rui Wang; Rong-Rong Zhu; Rong Xiao; Hui Liu; Shi-Long Wang (Biological Trace Element Research, 2011)

Pollen morphology of Hosta Tratt. in China and its taxonomic significance - Jia-Xi Liu; Chun-Hai Zhao; Xiao-Rui Liu; Yi-Zhen Xi; Yu-Long Zhang (Plant Systematics and Evolution, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Effects of arbuscular mycorrhizal fungi on zinnia and the different colonization between Gigaspora and Glomus - Liang-Kun Long; Qing Yao; Yong-Heng Huang; Rui-Heng Yang; Jun Guo; Hong-Hui Zhu (World Journal of Microbiology and Biotechnology, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

Dynamics of soil organic carbon and nitrogen associated with physically separated fractions in a grassland-cultivation sequence in the Qinghai-Tibetan plateau - Xiao Ming Shi; Xiao Gang Li; Rui Jun Long; Bhupinder Pal Singh; Zhuo Ting Li; Feng Min Li (Biology and Fertility of Soils, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Dynamics of soil properties and organic carbon pool in topsoil of zokor-made mounds at an alpine site of the Qinghai–Tibetan Plateau - Xiao Gang Li; Mei Lan Zhang; Zhuo Ting Li; Xiao Ming Shi; Qifu Ma; Rui Jun Long (Biology and Fertility of Soils, 2009)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Identification and characterization of cyclin X which activates transcriptional activities of c-Myc - Xuanyang Li; Xiang Wang; Guoyuan Liu; Rui Li; Long Yu (Molecular Biology Reports, 2009)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Cloning of three members of acc synthase gene family in sugarcane - Ai-Qin Wang; Li-Tao Yang; Zi-Zhang Wang; Yu-Tuo Wei; Long-Fei He; Yang-Rui Li (Sugar Tech, 2006)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)